2017
DOI: 10.1007/s11465-017-0408-3
|View full text |Cite
|
Sign up to set email alerts
|

Precision glass molding: Toward an optimal fabrication of optical lenses

Abstract: It is costly and time consuming to use machining processes, such as grinding, polishing and lapping, to produce optical glass lenses with complex features. Precision glass molding (PGM) has thus been developed to realize an efficient manufacture of such optical components in a single step. However, PGM faces various technical challenges. For example, a PGM process must be carried out within the super-cooled region of optical glass above its glass transition temperature, in which the material has an unstable no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 79 publications
0
29
0
Order By: Relevance
“…To date, several comprehensive reviews have been reported that summarize the key issues associated with the precision glass molding process [ 29 ], which are issues related to the replication of non-spherical glass lenses [ 30 ], theoretical and technological advancement of current glass molding [ 31 ], chalcogenide glass for infrared (IR) optics [ 32 ], and the manufacturing of optical micro-components via glass molding [ 33 ]. However, despite the mold being an indispensable component of micro/nano glass molding, there has been no review of the fabrication of these molds.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several comprehensive reviews have been reported that summarize the key issues associated with the precision glass molding process [ 29 ], which are issues related to the replication of non-spherical glass lenses [ 30 ], theoretical and technological advancement of current glass molding [ 31 ], chalcogenide glass for infrared (IR) optics [ 32 ], and the manufacturing of optical micro-components via glass molding [ 33 ]. However, despite the mold being an indispensable component of micro/nano glass molding, there has been no review of the fabrication of these molds.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring friction of contacts formed between solids and glasses at temperatures close to the glass transition is a problem of both fundamental scientific interest and technological relevance. Concerning technological applications, understanding the tribological mechanisms is particularly relevant for precision glass molding (PGM) [1][2][3][4], where optical components are formed in a one-step process from heated glass by using molds made typically from tungsten carbide (WC) with a precisely machined and smooth surface. Since the production of the pressing tools, i.e., the molds, is an expensive and complex process, their lifetime ultimately determines the economic viability of the method.…”
Section: Introductionmentioning
confidence: 99%
“…Three thousand years after its first appearance, commercial optical lenses are still prepared by either mechanical polishing or molding of rigid materials, such as glass [6] or plastics [7], and optical microscopes still rely on the use of lenses as a light collection element (for reflected, emitted, and/or diffracted light) and discrete optical filters for light manipulation (e.g. wavelength selection and/or intensity modulation) [8].…”
Section: Introductionmentioning
confidence: 99%